2015
DOI: 10.1260/1369-4332.18.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Local Plasticity Using Lamb Waves

Abstract: An experimental method was developed to monitor local plasticity in metallic materials using Lamb waves. A double-edge-notched beam specimen under tensile loading was employed to induce the local plasticity in notch area. By exciting Lamb waves using actuators in two different ways, the obtained wave signals at different stress levels of the specimen were analyzed through wavelet analysis by proposing a signal index I. By virtue of the finite element analysis on the tensile behavior of the specimen, it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…At the low frequency-thickness product ( f • d), the S 0 wave propagates with less dispersion and is therefore more suitable for measuring the elastic characteristics of thin plates or detecting their possible defects [22,23]. For example, studies have shown that low-frequency S 0 waves can be used to assess the damage of plasticity [24] and cracks [25][26][27]. When detecting defects with S 0 waves, the reflected waves of A 0 waves at the edges of thin plates or at the edges of defects can cause superposition, which will cause great difficulties in data analysis [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…At the low frequency-thickness product ( f • d), the S 0 wave propagates with less dispersion and is therefore more suitable for measuring the elastic characteristics of thin plates or detecting their possible defects [22,23]. For example, studies have shown that low-frequency S 0 waves can be used to assess the damage of plasticity [24] and cracks [25][26][27]. When detecting defects with S 0 waves, the reflected waves of A 0 waves at the edges of thin plates or at the edges of defects can cause superposition, which will cause great difficulties in data analysis [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…An effective and reliable inspection technique for continuous monitoring and evaluation of early-stage nonlinearities in materials is necessary for engineering parts. Among all kinds of nondestructive methods studied for efficient damage detection and evaluation, the ultrasonic method is most useful and has been widely exploited for many decades [ 1 , 2 , 3 , 4 ]. Traditional ultrasonic inspection and monitoring methods are usually anchored on linear theory, and the characterization parameters are velocity attenuation, transmission, and reflection coefficients of the ultrasonic wave.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional ultrasonic inspection and monitoring methods are usually anchored on linear theory, and the characterization parameters are velocity attenuation, transmission, and reflection coefficients of the ultrasonic wave. However, conventional linear ultrasonic evaluation and monitoring methods are not sensitive to early stage micro-damage or micro-plastic deformation [ 4 ], and the smallest crack that current linear ultrasonic based approaches can monitor or evaluate is only approximately 1 mm [ 5 ]. This drawback limits their applications and does not allow early preventive actions [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%